Clinical case of exudative pericarditis in a child after pacemaker implantation - A. V. Serezhkina; A. A. Bulka; I. G. Khmelevskaya; N. S. Razinkova; T. A. Minenkova; O. G. Bets; А. А. Sosnovskaya (Лечащий Врач, 2022)
Pericarditis is a common pericardial disease in clinical practice. The disease implies the occurrence of inflammation of the sheets of the pericardium and the surface layers of the myocardium with the further formation of a pleural effusion or without it. There are no reliable data on the prevalence of pericarditis in pediatrics, which is explained by difficulties in diagnosis, especially in younger patients. Signs of the disease are detected at autopsy in 2-12% of cases. Most pericarditis proceeds favorably, but complications such as cardiac tamponade and constrictive pericarditis pose a direct threat to the life of the child. The causes of this disease can be infectious diseases, systemic connective tissue diseases, allergic and autoimmune diseases, heart and pericardial surgery, local radiation injury, metabolic disorders. The main symptoms of pericarditis are pain behind the sternum or in the left half of the chest, a feeling of pressure or heaviness, shortness of breath, a feeling of lack of air, cough. The severity of clinical manifestations depends on the amount of fluid in the pericardial cavity and on the rate of its accumulation, and the nature of the underlying disease plays an important role. In the diagnosis of pericarditis, such research methods as chest x-ray, multislice computed tomography, echocardiography, and electrocardiography are of particular importance. To verify the diagnosis and clarify the cause of exudation, a pericardial puncture is performed. The erroneous opinion of doctors about pericarditis as a rare disease leads to the late detection of this pathology and worsening of the prognosis, and the incorrect interpretation of the results obtained during instrumental studies plays an important role. It must be remembered that pericarditis most often occurs as a complication of the underlying disease, so doctors should pay special attention to the cardiovascular system when examining patients. This article presents a clinical case of exudative pericarditis without cardiac tamponade of unknown etiology after implantation of a single-chamber pacemaker, diagnosed in a child aged 5 years 11 months. The dynamics of clinical manifestations is noted, the entire range of studies conducted for the patient in the hospital is reflected, with interpretations of the conclusions, symptomatic treatment schemes are given.